THE IMPACTS OF BUDGET DECENTRALIZATION ON ECONOMIC GROWTH AND LOCAL GOVERNMENT PERFORMANCE - Agus Samekto (Universitas Hayam Wuruk Perbanas, 2012)
The implementation of decentralization can cause an expansion of authorities for local governmentand also be expected to encourage the improvement of local financial capability.Besides that, decentralization tends to allow larger authorities for local government to manageand maintain the local area, including financial management, so it finally enables localgovernment to be easier to increase their creativity in developing the local potential. Thisresearch is aimed to analyze the impacts of budget decentralization on supporting economicgrowth and improving local government performance of residences/cities in East Java. Researchpopulation is the whole local government of residences/cities in East Java, consistingof 29 residences and 9 cities. Analysis technique used in this research is partial least square(PLS). The results show that in East Java: (1) Budget decentralization of residences/citiesprovides significant impact on economic growth (2) On the contrary; budget decentralizationof residences/cities does not provide significant impact on local government performance. (3)Economic growth in residences/cities statistically provides significant impact toward localgovernment performance. (4) Budget decentralization of residences/cities statistically providessignificant impact on local government performance through economic growth.